Understanding the effects of personal responsibility and environment on the development of self-directed learning: an exploratory study - Carlisle, Vincent J. (Kansas State University, 2016)
This exploratory study analyzed changes in self-directed learning of Army officers attending the Army’s Command and General Staff Officers Course, CGSOC, by applying a quasi-experimental, pretest posttest, comparative approach based on the attribute independent variables gender, race/ethnicity, level of education, and branch of Army. It also sought to inform implementation and assessment strategies in both the private and broader public sectors, specifically companies and organizations seeking to develop lifelong learners in the furtherance of creating or sustaining a learning organization. The study began with the administration of the Personal Responsibility Orientation to Self-directed Learning Scale (PRO-SDLS) during the first week of a ten-month resident course and concluded with a second administration of the PRO-SDLS at the end of the course. In addition to a total score, the PRO-SDLS provided results for four dependent variables: learner initiative, learner self-efficacy, learner control, and learner motivation. Though effect size varied, this study found a statistically significant difference in pretest to posttest scores differences between white and non-white in both total score and in the subcomponent of learner motivation. Additionally, the change in scores for learner motivation from pretest to posttest for whites was statically significant. Finally, the change in scores for the subcomponent of learner control between students with a bachelor’s degree and those with a master’s degree was also significant. The broader implication of these findings is the caution by Brockett and Hiemsta (1991) that adult educators should consider the individual characteristics of the learner when developing and delivering curriculum. In this case it would appear that either the curriculum or the delivery of the curriculum or a combination of the two may have been experienced differently by white and non-white Army officers; specifically regarding the development of learner motivation.
Keywords: PRO-SDLS; Learner control; Learner initiative; Learner self-efficacy; Learner motivationSelf-directed learning